1998
DOI: 10.1080/09540129848307
|View full text |Cite
|
Sign up to set email alerts
|

Cultures of sexual adventurism as markers of HIV seroconversion: A case control study in a cohort of Sydney gay men

Abstract: A case control analysis within an ongoing cohort study was used to examine differences between seroconverters and men who remained HIV-negative. The cases were interviewed within one to 13 months prior to their seroconversion. Their responses to a structured questionnaire were compared with those of HIV-negative controls drawn from the same time period and from the same longitudinal study, Sydney Men and Sexual Health. Data collected from both cases and controls included: demographic and contextual variables, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
79
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(84 citation statements)
references
References 7 publications
4
79
0
1
Order By: Relevance
“…According to the above-mentioned study carried out in Sydney, Australia, homosexual men who engaged in unconventional sexual activities were at higher risk of acquiring HIV, probably due to the fact that they looked for partners within particular sexual subcultural contexts. 28 In the same way as with paraphilias and SC, there was a more frequent history of sexual violence in group 1. 20,29 Although group 1 had higher risk of STD and HIV infections and use of "morning after pill," there was more reference to fear of contracting STD in this group, a fact that can be associated with higher frequency of sexual activity.…”
Section: Discussionmentioning
confidence: 77%
“…According to the above-mentioned study carried out in Sydney, Australia, homosexual men who engaged in unconventional sexual activities were at higher risk of acquiring HIV, probably due to the fact that they looked for partners within particular sexual subcultural contexts. 28 In the same way as with paraphilias and SC, there was a more frequent history of sexual violence in group 1. 20,29 Although group 1 had higher risk of STD and HIV infections and use of "morning after pill," there was more reference to fear of contracting STD in this group, a fact that can be associated with higher frequency of sexual activity.…”
Section: Discussionmentioning
confidence: 77%
“…One potential underlying factor may involve sexual adventurism [35]. Men who tend toward higher-risk sexual behavior, and who are therefore more vulnerable to infection, may also be less inclined toward having monogamous partnerships.…”
Section: Discussionmentioning
confidence: 99%
“…35 Although most of these activities do not appear to pose an HIV transmission risk in themselves, a case-control study of gay men in Sydney found that engagement in 'esoteric' practices including fisting, sadomasochism and use of sex toys was an important predictor of whether men acquired HIV. 36 Sexually adventurous men who engage in such esoteric practices may be at heightened risk for HIV because they seek partners within particular sexual subcultures. One important purpose of the study reported here is to 'anchor' the estimates obtained from targeted gay community research such as Male Call 35 and the gay community cohort studies 36 to a representative household sample.…”
Section: Esoteric Practicesmentioning
confidence: 99%